Iodine nutritional status, the prevalence of thyroid goiter and nodules in rural and urban residents: a cross-sectional study from Guangzhou, China. Issue 12 (29th November 2021) - Yan, Yuerong; You, Lili; Wang, Xiaoyi; Zhang, Zhuo; Li, Feng; Wu, Hongshi; Wu, Muchao; Zhang, Jin; Wu, Jiayun; Chen, Caixia; Li, Xiaohui; Xia, Biwen; et al.
Abstract : Objectives: A variety of factors differed between rural and urban areas may further influence iodine status and thyroid structure. Hence, this study compared iodine nutrition, the prevalence of thyroid goiter, and nodules between rural and urban residents in Guangzhou, a southern coastal city of China. Methods: A total of 1211 rural residents and 1305 urban residents were enrolled in this cross-sectional study. A questionnaire regarding personal characteristics was administered. Urinary iodine concentration (UIC) was examined. Ultrasonography of the thyroid was performed to evaluate thyroid goiter and nodules. Multiple logistic analysis was used to identify the potential associated factors. Results: The median UIC was significantly lower in rural residents than in urban residents (120.80 μg/L vs 136.00 μg/L, P < 0.001). Although the coverage rate of iodized salt was much higher in rural residents than in urban residents (99.59% vs 97.29%, P < 0.001), the percentages of seafood intake (8.60% vs 29.29%, P < 0.001), iodine-containing drug consumption (0.33% vs 1.24%, P = 0.011), and iodine contrast medium injection (0.58% vs 1.87%, P = 0.004) were lower in rural residents than in urban residents. Both the prevalence of thyroid goiters and nodules was significantly higher in rural residents than in urban residents (goiter: 8.06% vs 1.20%, P < 0.001; nodules: 61.89% vs 55.04%, P = 0.023). Living in rural areas was associated with thyroid goiter (OR 5.114, 95% CI 2.893–9.040, P < 0.001). Conclusions: There were differences in iodine nutrition and the prevalence of thyroid goiter and nodules in rural and urban residents in Guangzhou. Differentiated and specialized monitoring is recommended in our area.